Synthesis of benzo[d]imidazo[2,1-b]benzoselenoazoles: Cs2CO3-mediated cyclization of 1-(2-bromoaryl)benzimidazoles with selenium - Matsumura, Mio; Kitamura, Yuki; Yamauchi, Arisa; Kanazawa, Yoshitaka; Murata, Yuki; Hyodo, Tadashi; Yamaguchi, Kentaro; Yasuike, Shuji (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of benzimidazo[2,1-b]benzoselenoazoles is described. The novel ring-closure reaction of 1-(2-bromoaryl)benzimidazoles with Se powder is promoted by Cs2CO3 (2 equiv) in DMF at 150 °C. Moreover, the obtained tetracyclic heterocycles are all novel compounds. Single-crystal X-ray analysis of the parent benzimidazo[2,1-b]benzoselenoazole revealed that the tetracyclic ring is almost planar. Absorption spectroscopy data of the benzimidazo[2,1-b]benzoselenoazoles showed the λmax was dependent on the number of rings.
Keywords: benzimidazole; cesium carbonate; cyclization; selenium; selenoazole

Product Subclass 7: Benzo[b]selenophenes - Murphy, P. J. (Georg Thieme Verlag, 2001)

(untitled) - Skhiri, A.; Ben Salem, R.; Soulé, J.-F.; Doucet, H. (ChemCatChem, 2017)

(untitled) - Ninomiya, M.; Garud, D. R.; Koketsu, M. (Coord. Chem. Rev., 2011)

(untitled) - Paegle, E.; Domracheva, I.; Turovska, B.; Petrova, M.; Kanepe-Lapsa, I.; Gulbe, A.; Liepinsh, E.; Arsenyan, P. (Chem. – Asian J., 2016)

French Patent - Sevrin, M.; Peretti, D. D.; George, P. (Imidazo[2,1-b]benzoselenazole-3-acetamide Derivatives, Their Preparation, and Their Therapeutic Application, 1994)

(untitled) - Roehrs, J. A.; Pistoia, R. P.; Back, D. F.; Zeni, G. (Adv. Synth. Catal., 2012)

(untitled) - Grimaldi, T. B.; Godoi, B.; Roehrs, J. A.; Sperança, A.; Zeni, G. (Eur. J. Org. Chem., 2013)

(untitled) - Kumar, R. K.; Manna, S.; Mahesh, D.; Sar, D.; Punniyamurthy, T. (Asian J. Org. Chem., 2013)

(untitled) - Ranu, B. C.; Dey, R.; Chatterjee, T.; Ahammed, S. (ChemSusChem, 2012)

(untitled) - Beletskaya, I. P.; Ananikov, V. P. (Chem. Rev., 2011)

Catalyzed carbon-heteroatom bond formation - Beletskaya, I. P.; Ananikov, V. P. (The formation of Csp2–S and Csp2–Se bonds by substitution and addition reactions catalyzed by transition metal complexs, 2011)

(untitled) - Qiao, J. X.; Lam, P. Y. S. (Synthesis, 2011)

(untitled) - Beletskaya, I. P.; Ananikov, V. P. (Eur. J. Org. Chem., 2007)

(untitled) - Luo, D.; Wu, G.; Yang, H.; Liu, M.; Gao, W.; Huang, X.; Chen, J.; Wu, H. (J. Org. Chem., 2016)

(untitled) - Matsumura, M.; Sakata, Y.; Iwase, A.; Kawahata, M.; Kitamura, Y.; Murata, Y.; Kakusawa, N.; Yamaguchi, K.; Yasuike, S. (Tetrahedron Lett., 2016)

(untitled) - Sun, P.; Jiang, M.; Wei, W.; Min, Y.; Zhang, W.; Li, W.; Yang, D.; Wang, H. (J. Org. Chem., 2017)

(untitled) - Diness, F.; Fairlie, D. P. (Angew. Chem., Int. Ed., 2012)

(untitled) - Gao, Z.; Zhu, X.; Zhang, R. (RSC Adv., 2014)

(untitled) - Zou, L.-H.; Reball, J.; Mottweiler, J.; Bolm, C. (Chem. Commun., 2012)

(untitled) - Saito, M.; Kanatomi, Y. (J. Sulfur Chem., 2009)

(untitled) - Varala, R.; Ramu, E.; Adapa, S. R. (Bull. Chem. Soc. Jpn., 2006)

(untitled) - Ma, X.; Liu, Q.; Jia, X.; Su, C.; Xu, Q. (RSC Adv., 2016)